Evolutionary Significance of the Neuroendocrine Stress Axis on Vertebrate Immunity and the Influence of the Microbiome on Early-Life Stress Regulation and Health Outcomes - Ortega, Van A.; Mercer, Emily M.; Giesbrecht, Gerald F.; Arrieta, Marie-Claire (Frontiers in Microbiology, 2021)
Stress is broadly defined as the non-specific biological response to changes in homeostatic demands and is mediated by the evolutionarily conserved neuroendocrine networks of the hypothalamus-pituitary-adrenal (HPA) axis and the sympathetic nervous system. Activation of these networks results in transient release of glucocorticoids (cortisol) and catecholamines (epinephrine) into circulation, as well as activation of sympathetic fibres innervating end organs. These interventions thus regulate numerous physiological processes, including energy metabolism, cardiovascular physiology, and immunity, thereby adapting to cope with the perceived stressors. The developmental trajectory of the stress-axis is influenced by a number of factors, including the gut microbiome, which is the community of microbes that colonizes the gastrointestinal tract immediately following birth. The gut microbiome communicates with the brain through the production of metabolites and microbially-derived signals, which are essential to human stress response network development. Ecological perturbations to the gut microbiome during early life may result in the alteration of signals implicated in developmental programming during this critical window, predisposing individuals to numerous diseases later in life. The vulnerability of stress response networks to maladaptive development has been exemplified through animal models determining a causal role for gut microbial ecosystems in HPA axis activity, stress reactivity, and brain development. In this review, we explore the evolutionary significance of the stress-axis system for health maintenance and review recent findings that connect early-life microbiome disturbances to alterations in the development of stress response networks.